Spectral deconvolution as a tool to understanding Curie-Temperature Shifting and Niobium Off-Centering Phenomenon in Ferroelectrics of Type Niobates - Lanfredi, S. [UNESP]; Nobre, M. A.L. [UNESP]; Besse, M. R. [UNESP]; Lima, A. R.F.; Palacio, G. [UNESP] (Hikari, 2015)
Solid solutions based on the KSr2Nb5O15 host-structure with stoichiometry KSr2(NixNb5-x)O15-δ, where x = 0.25, 0.50 and 0.75 were synthesized. Single phase nanopowders were synthesized via Modified Poliol method. Both X-ray diffraction and Infrared spectroscopy were used to derive the magnitude of the niobium off-center. Curie temperature was derived by X-ray diffraction measurements and Infrared spectroscopy. Deconvolution of the infrared spectra based on a set of Gaussian functions was applied to derive oscillating frequency assigned to the bond niobium off-center apical oxygen, while crystallographic parameters were derived via Rietveld Method. The shifting of Nb cation along of c-axis and its correlation with to octahedra distortion allowed to derive further inter-correlation between niobium-offcenter degree and softening phenomena. Curie-temperature shifting to low temperature domain as a function of doping of host structure with Ni cation is discussed.
Keywords: Deconvolution; Force constant; Gaussian function; Infrared spectroscopy; Niobium off-center